2022
DOI: 10.3389/fendo.2022.1021420
|View full text |Cite
|
Sign up to set email alerts
|

Silent pheochromocytoma and paraganglioma: Systematic review and proposed definitions for standardized terminology

Abstract: Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors with heterogeneous clinical presentations and potential lethal outcomes. The diagnosis is based on clinical suspicion, biochemical testing, imaging and histopathological confirmation. Increasingly widespread use of imaging studies and surveillance of patients at risk of PPGL due to a hereditary background or a previous tumor is leading to the diagnosis of these tumors at an early stage. This has resulted in an increasing use of the ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 141 publications
0
19
0
Order By: Relevance
“…PUB is an exceedingly rare entity, accounting for only 1% of all pheochromocytomas and 0.05% of all bladder tumors [ 1 ]. The clinical presentation of PUB can be diverse, and it may mimic other urinary conditions, making it challenging to diagnose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUB is an exceedingly rare entity, accounting for only 1% of all pheochromocytomas and 0.05% of all bladder tumors [ 1 ]. The clinical presentation of PUB can be diverse, and it may mimic other urinary conditions, making it challenging to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…Pheochromocytoma is a rare catecholamine-secreting neuroendocrine tumor predominantly arising from chromaffin cells in the adrenal medulla. However, approximately 10% of these tumors can arise from extra-adrenal locations, known as paragangliomas [ 1 , 2 ]. Paraganglioma of the urinary bladder (PUB) is an exceptionally rare extra-adrenal location, accounting for only 0.05% of all bladder tumors and 1% of all pheochromocytomas, with only about 200 cases reported literature [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of plasma or urinary metanephrines are negative in the large majority of HNPGLs and may be false negative in patients with small PPGLs, and in rare cases of nonfunctional PPGLs ( 66 ). In these cases, the diagnosis may primarily rely on PPGL-specific imaging.…”
Section: Clinical Scenario I: the Role Of Imaging At The Initial Diag...mentioning
confidence: 99%
“…5 Despite being biochemically negative, these tumours still carry the risk of catecholamine crisis as they may be functional. 6 Review of published cases revealed perioperative haemodynamic instability in 12 of 13 patients with biochemically negative phaeochromocytomashypertensive crises in six, significant hypotension in eight and Takotsubo cardiomyopathy in one, despite preoperative phenoxybenzamine of variable duration in five patients. 4,8,9 Genetic mutations were found in 12 out of 16 patients tested -SDHB (5), MEN2A (4), VHL (2) and SDHD (1).…”
mentioning
confidence: 98%
“…Fewer than 40 biochemically negative phaeochromocytomas have been described. [4][5][6] Characteristic features of phaeochromocytoma on CT include density >10 HU, delayed washout and cystic or haemorrhagic changes. 7 High signal intensity on T2-weighted images on MRI are characteristic of phaeochromocytoma.…”
mentioning
confidence: 99%